Case Report: A Case of Cotton-Wool Spots After Intravitreal Injection of Conbercept in an Infant With Incontinentia Pigmenti - Liang, Licong; Yang, Yiliu; Bu, Shaochong; Lu, Fang (Frontiers in Medicine, 2021)
Introduction: Incontinentia pigmenti (IP) is a rare X-linked neuroectodermal dysplasia affecting multiple organs. One of the most significant ophthalmic manifestations is retinal neovascularization due to retinal ischemia, which has been traditionally treated with laser photocoagulation or cryotherapy. The application of anti-vascular endothelial growth factor (VEGF) has been reported for the treatment of retinopathy of IP with beneficial results. However, clinicians should be aware of the possible ocular and systemic side effects of intravitreal injection of anti-VEGF agents. Case report: A four-month-old female infant with IP was treated with intravitreal injection of conbercept in both eyes. However, cotton-wool spots were noticed in the left eye one week after the injection. Laser photocoagulation was performed as an adjunct treatment. The cotton-wool spots absorbed one month after the first intravitreal injection and eventually disappeared. Discussion: The cotton-wool spots after intravitreal injection of conbercept for the treatment of IP indicated severe retinal ischemia resulting from the neutralization of excessive VEGF, which was shown on fundus photograph and fluorescent angiography. Anti-VEGF agents could cause retinal arteriolar vasoconstriction and artery occlusion on rare occasions. The administration of anti-VEGF agents in pediatric cases with severe neovascularization and retinal ischemia should be carefully considered.